2009
DOI: 10.2527/jas.2009-1931
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships among growth, endocrine, immune, and temperament variables in neonatal Brahman calves

Abstract: Interrelationships among growth, endocrine, immune, and temperament variables were assessed in neonatal Brahman calves. The velocity upon exiting a working chute (exit velocity) of an animal was measured and used as an objective indicator of temperament to classify calves as calm, intermediate, or temperamental. Calves (n = 116) were weighed weekly between d 0 and 21 to 24, and blood samples were collected for plasma and serum on d 0, 1, 2, 7, 14, and 21 to 24 after birth to measure concentrations of immunoglo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 34 publications
4
34
0
1
Order By: Relevance
“…27 The minimum detectable cortisol concentration was 1.2 ng/ml and the intraand interassay coefficients of variance were 4.3% and 2.4%, respectively. Serum concentrations of cortisol were determined by comparison to a standard curve generated with known concentrations of cortisol and presented as the concentration in nanogram per millilitre.…”
Section: Assays For Cortisol and Epinephrinementioning
confidence: 99%
See 1 more Smart Citation
“…27 The minimum detectable cortisol concentration was 1.2 ng/ml and the intraand interassay coefficients of variance were 4.3% and 2.4%, respectively. Serum concentrations of cortisol were determined by comparison to a standard curve generated with known concentrations of cortisol and presented as the concentration in nanogram per millilitre.…”
Section: Assays For Cortisol and Epinephrinementioning
confidence: 99%
“…27 Data are presented as picogram per millilitre. The minimum detectable epinephrine concentration was 11 pg/ml and the intra-and interassay coefficients of variation were 3.7% and 7.4%, respectively.…”
Section: Assays For Cortisol and Epinephrinementioning
confidence: 99%
“…Serum concentrations of cortisol were determined using a single antibody radioimmunoassay (DSL-2100; Diagnostic Systems Labs, Webster, TX) utilizing rabbit anti-cortisol antiserum coated tubes according to the manufacturer's directions (Burdick et al, 2009). The minimum detectable cortisol concentration was 1.2 ng/mL and the intra-and interassay coefficients of variation were 4.3% and 2.4%, respectively.…”
Section: Cortisolmentioning
confidence: 99%
“…Plasma concentrations of epinephrine were determined by enzyme immunoassay according to the manufacturer's directions (17-BCTHU-E02; Alpco Diagnostics, Boston, MA; Burdick et al, 2009) by comparison of unknowns to standard curves generated with known concentrations of epinephrine. Data are presented as pg/mL.…”
Section: Epinephrinementioning
confidence: 99%
“…Stressful conditions lead to elevated plasma cortisol concentrations, which may also be related to PSE meat, especially in pigs (Chai et al, 2010). In calves, temperament and excitability were assessed and it was reported that cortisol and catecholamines are produced when calves experience acute stress during weaning (Burdick et al, 2009;O'Neill et al 2010). In human beings, cortisol levels are reported to have increased owing to related abnormal behaviour (Haller et al, 2005) whereas in animals they were related to aggressive and antagonistic behaviour (Reisnet et al, 2007).…”
Section: Catecholamines Cortisol and Glucocorticoidsmentioning
confidence: 99%